2004
DOI: 10.1111/j.1439-0523.2004.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPD markers linked with restorer genes for the C‐source of cytoplasmic male sterility in rye (Secale cereale L.)

Abstract: The study was aimed at the identification of random amplified polymorphic DNA markers linked to genes controlling male sterility in rye with the C-source of sterility-inducing cytoplasm. Markers of male sterility were distinguished using bulk segregant analysis, carried out on the two F 2 crosses between male sterile and male fertile inbred lines. Screening of polymorphisms revealed by 1000 arbitrary 10-mer primers allowed the detection of 10 markers in the cross between 711-cmsC and DS2 lines and seven marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Quantitative trait loci (QTL) analysis allowed for the localisation of additional less efficient restorers on chromosomes 2A, 4B and 6A (Ahmed et al 2001). In rye (the second ancestor of the triticale), QTL analyses performed on F 2 mapping populations resulted in the detection of genes restoring male fertility in CMS systems on chromosomes 1R, 3R, 4R, 5R and 6R (Miedaner et al 2000; Stojałowski et al 2004). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative trait loci (QTL) analysis allowed for the localisation of additional less efficient restorers on chromosomes 2A, 4B and 6A (Ahmed et al 2001). In rye (the second ancestor of the triticale), QTL analyses performed on F 2 mapping populations resulted in the detection of genes restoring male fertility in CMS systems on chromosomes 1R, 3R, 4R, 5R and 6R (Miedaner et al 2000; Stojałowski et al 2004). …”
mentioning
confidence: 99%
“…The significance of genotype by environment interactions for the detection of QTL controlling different traits is usually investigated by the assessment of “immortal” mapping populations (recombinant inbred lines, DH lines) or by the verification of results from F 2 in the F 3 generation. Unfortunately, research on male sterility restoration is frequently limited to the one generation (Miedaner et al 2000; Stojałowski et al 2004) because the reproduction of male sterile genotypes by self-pollination is impossible. Application of the partial F 3 generation obtained from only fertile plants can be recommended for the identification of heterozygous F 2 plants, which is reasonable for investigations on one effective restorer gene (Börner et al 1998; Hackauf et al 2012).…”
mentioning
confidence: 99%
“…The source material for this population was a hybrid between male-sterile inbred line 544C containing the C cytoplasm and the restorer inbred line Ot0-20. Research conducted on the F 2 generation of this hybrid indicated that the paternal line contained at least two effective restorer genes and that one of the supposed genes was located on the 4RL chromosome (Stojałowski et al 2004 ). The male-fertile hybrid plants from the F 1 and following generations were used for consecutive back-crossing with male-sterile line 544C.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear genes that restore male fertility in rye with Pampa and Vavilovii cytoplasms are spread throughout the rye genome; rough mapping analyses have indicated that they are localized on chromosomes 1R, 3R, 4R, 5R, and 6R (Börner et al 1998 ; Miedaner et al 2000 ; Bednarek et al 2002 ; Stojałowski et al 2004 ). Among these genes, those most efficient at fertility restoration were located on the long arm of chromosome 4R.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR amplifications were performed using a PTC‐200 thermocycler (MJ Research) as follows: initial denaturation at 95°C for 1 min, followed by 10 cycles of denaturation at 94°C for 5 s, annealing at 37°C for 30 s and elongation at 72°C for 30 s, followed by 35 cycles at temperatures: 94°C for 5 s, 37°C for 30 s and 72°C for 1 min. The final extension was performed for 7 min at 72°C (Stojalowski et al ., 2004). Amplicons were detected by electrophoresis on a 1·5% agarose gel with 0·5 × TBE buffer, stained with ethidium bromide and photographed using a digital camera and a UV trans‐illuminator.…”
Section: Methodsmentioning
confidence: 99%